Communication Networking in Chain Supply Information Management Among Indonesian MSMEs - Yuliana Rakhmawati; Inka Munika; Nikmah Suryandari; Farida Nurul Rahmawati; Netty Dyah Kurniasari; Prasetyono Prasetyono (Jurnal ILMU KOMUNIKASI, 2026)
Indonesian tempeh micro, small, and medium enterprises (MSMEs) establish communication networks to address soybean raw materials and distribution challenges during the COVID-19 outbreak. This study aims to analyze the communication network structure among 204 tempeh entrepreneurs through centrality and actor-level analysis. The findings reveal that within the network structure, nodes serve as bridges, hubs, and cut points among entrepreneurs in raw materials and product distribution issues. The established communication network reflects a complex cybernetic pattern involving centrality and actor participation. The Sahabat Pengrajin Tempeh Pekalongan  (SPTP) Indonesia network is centralized without isolation.